(untitled) (Practitioner Research, 2023)
This study set out to find out how Malaysian Polytechnic English language instructors felt about the Common European Framework of Reference for Languages’ launch (CEFR). The literature review highlighted the issues with changing policies, adapting curricula, and the difficulties experienced by English language teachers. 30 English educators of different Malaysian polytechnics were approached and requested to complete a self-administered questionnaire via Google Forms to obtain the data. The response was analyzed for reliability and validity with Cronbach’s alpha and Exploratory Factor Analysis (EFA). Three key factors were recognized and validated using Exploratory Factor Analysis: the educators’ familiarity, the educators’ acceptance, and the educators’ challenges. The questionnaire, which consists of 15 items and uses a 6-point Likert scale with 5 = Agree, 4 = Slightly Agree, 3 = Slightly Disagree, 2 = Disagree, and 1 = Strongly Disagree, has been shown to be extremely dependable.